Therapeutic Drug Monitoring of Sirolimus, Correlation With Laboratory Parameters In Transplant Patients: Therapeutic drug monitoring of sirolimus - Hashem Montaseri; Hasan Merrikhi; Mohammad Javad Khoshnoud; Bita Geramizadeh (Iranian Journal of Pharmaceutical Sciences, 2011)
Sirolimus is a potent immunosuppressive agent administered as prophylactic agent to prevent rejection after organ transplantation. Sirolimus must be used within a narrow therapeutic window. Due to inter- and intra-variability, sirolimus blood concentrations may be affected, therefore, there is no possibility of predicting the sirolimus blood concentrations based on the dose patients received. Therapeutic drug monitoring (TDM) of whole blood is an important part of immunosuppressive therapy and is mandatory for sirolimus dosage individualization. The objective of this study was to present a validated method for the analysis of sirolimus in human blood by LC/MS spectrometry and also evaluation of correlation between blood sirolimus concentration and laboratory parameters. We examined a group of 32 patients receiving sirolimus at different stages after organ (kidney, liver or pancreas) transplantation. The mean sirolimus concentration was 10.2 ng/ml (range: 1.330.1 ng/ml).The assay was validated for a linear dynamic range of 1-50 ng/ml. The correlation coefficient (r) was 0.995. The within-run imprecision CV(%) for concentrations (1 and 10 ng/ml) were 14.7 and 2.2%, respectively. The betweenrun imprecision CV(%) for the same concentrations were 14.8 and 3.4%, respectively. Limit of quantification (LOQ) and limit of detection (LOD) were defined as 1 and 0.3 ng/ml, respectively. Analytic recovery was 98±2% over a range of 1-50 ng/ml. Statistical results showed no correlation between sirolimus blood concentration and the dosage in patients receiving sirolimus. Also, no relationship between drug concentration in blood and laboratory parameters was seen.